3D ordered macroporous TiO2-supported Pt@CdS core–shell nanoparticles: design, synthesis and efficient photocatalytic conversion of CO2 with water to methane1. Issue 20 (28th May 2015) - Wei, Yuechang; Jiao, Jinqing; Zhao, Zhen; Zhong, Wenjia; Li, Jianmei; Liu, Jian; Jiang, Guiyuan; Duan, Aijun
<x xml:space="preserve">Abstract</x> 3DOM Pt@CdS/TiO2 catalysts exhibit super photocatalytic performance for CO2 reduction with H2O to CH4 under simulated solar irradiation.